Aerial navigation - Pellet, Henry Leamer (My University, 1893)
Introduction: Perhaps the greatest mechanical problem of the present day is that of successfully navigating the air. Ever since the earliest time man has had a desire to fly. There was the Darius of old with his wings of wax, which worked very successfully, until the sun became angry with him, and shining forth melted them, and caused his disastrous fall. Then we have our modern “Darius Green and his flying machine,” but even he did not reach the Forth of July celebration.
Citation: Pellet, Henry Leamer. Aerial navigation. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Navigation; Air; Wings; Darius green; Theses; Manuscripts (documents)